Korelasi Motivasi Belajar dan Prestasi Belajar Peserta Didik di SMTK Gloria Sentani Kabupaten Jayapura - Belwawin; Layan, Santy; Tasijawa, Riski; Tenison Murib (Sekolah Tinggi Agama Kristen Samarinda, 2024)
Abstract: This study investigates the relationship between learning motivation and academic achievement of students at SMTK Gloria Sentani, Jayapura Regency. Learning motivation is a crucial factor in achieving optimal academic performance. The research employs a correlational approach with a focus on the entire student population at SMTK Gloria Sentani, comprising 35 individuals. Data collection is conducted through a questionnaire using the Guttman scale. The analysis results indicate that the learning motivation of students at SMTK Gloria Sentani is still low, with an interpreted score of 29.6%. Meanwhile, the academic achievement of students correlates at 55.6%, indicating that motivational factors have an influence, albeit in a weak correlation level. Despite the weak correlation, learning motivation factors still contribute to students' academic performance. This research also reveals that some students exhibit low internal and external motivation, which may be a contributing factor to their low academic achievement. Abstrak: Studi ini menginvestigasi hubungan antara motivasi belajar dan prestasi belajar siswa di SMTK Gloria Sentani, Kabupaten Jayapura. Motivasi belajar adalah faktor penting dalam pencapaian prestasi belajar yang optimal. Penelitian ini menggunakan metode pendekatan korelasional dengan fokus pada seluruh populasi peserta didik di SMTK Gloria Sentani, yaitu 35 orang. Pengumpulan data dilakukan melalui kuesioner dengan skala Guttman. Hasil analisis menunjukkan bahwa motivasi belajar peserta didik di SMTK Gloria Sentani masih rendah, dengan interpretasi skor sebesar 29.6%. Sementara itu, prestasi belajar peserta didik berkorelasi sebesar 55.6%, menunjukkan bahwa faktor motivasi memiliki pengaruh, meskipun dalam tingkat korelasi yang lemah. Meskipun korelasinya lemah, faktor motivasi belajar tetap memberikan kontribusi terhadap prestasi belajar siswa. Hasil penelitian ini juga mengungkapkan bahwa sebagian siswa memiliki motivasi internal dan eksternal yang rendah, yang mungkin menjadi penyebab rendahnya prestasi belajar.